Association of High‐Density Lipoprotein Particles and High‐Density Lipoprotein Apolipoprotein C‐III Content With Cardiovascular Disease Risk According to Kidney Function: The Multi‐Ethnic Study of Atherosclerosis. Issue 24 (17th December 2019) - Lamprea‐Montealegre, Julio A.; McClelland, Robyn L.; Otvos, James D.; Mora, Samia; Koch, Manja; Jensen, Majken K.; de Boer, Ian H.
Abstract : Background: Chronic kidney disease is associated with structural and compositional abnormalities in high‐density lipoprotein particles (HDLp). We examined associations of HDLp size, particle subfractions, and apolipoprotein C‐III content with incident cardiovascular disease (CVD) events across categories of estimated glomerular filtration rate (eGFR). Methods and Results: Analyses included 6699 participants in MESA (Multi‐Ethnic Study of Atherosclerosis) with measurements of HDLp and 5723 participants with measurements of HDL apolipoprotein C‐III. Cox‐regression methods were used to evaluate associations between HDLp and apolipoproteins with CVD events. Larger HDLp size was associated with lower CVD risk in participants with lower eGFR: hazard ratio (95% CI) per SD higher mean HDL size was 1.00 (0.90–1.11) in eGFR ≥60 mL/min per 1.73 m 2, 0.65 (0.48–0.86) in eGFR 45 to 59 mL/min per 1.73 m 2, and 0.48 (0.25–0.93) in eGFR <45 mL/min per 1.73 m 2 ( P for interaction=0.05). Associations of HDLp subfractions with CVD varied significantly by eGFR ( P for interaction=0.04), with significant inverse associations between higher concentrations of large HDLp and CVD events across categories of kidney function, but nonsignificant results for small HDLp. Only HDLp without apolipoprotein C‐III was associated with lower risk of CVD events, with seemingly (albeit not statistically significant) stronger associations among participants with lower eGFR ( P for interaction=0.19). Conclusions: HDL particles of larger size and higher concentrations of large HDL and of HDL without apolipoprotein C‐III were associated with lower CVD risk, with risk estimates seemingly stronger among participants with lower eGFR. Future larger studies are needed to corroborate these findings.